Obremenjenost zraka s cvetnim prahom - Kofol-Seliger, Andreja (Naše okolje, 2022)
The pollen measurement has been performed on four sites in Slovenia: in Lendava in the Pomurje region, in the central part of the country in Ljubljana, and on the Adriatic coast in Izola. An outlook for the May is included in the article.
Keywords: alergeni; alergije; alergijske reakcije; cvetni prah